STRATEGI GURU PENDIDIKAN AGAMA KATOLIK DALAM MENINGKATKANKAN SELF-ESTEEM PESERTA DIDIK - Mimpin Sembiring; Windy Elyance Purba (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Self-confidence is an important aspect that supports students’ academic and social development. In the educational context, teachers are not only responsible for delivering learning materials but also for fostering students’ belief in their own abilities. This study examines the self-confidence of eleventh-grade students in Catholic Religious Education classes at SMA Katolik Cinta Kasih Tebing Tinggi, Medan, and explores the strategies employed by teachers to support its development. A descriptive qualitative approach was used, involving Catholic Religious Education teachers and eleventh-grade students as research participants. Data were collected through observation, interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The trustworthiness of the findings was ensured through source and technique triangulation.The findings indicate that the students demonstrated a good level of self-confidence, reflected in their willingness to express opinions, ability to manage emotions, independent learning habits, and awareness of their personal potential. These characteristics were supported by various teacher strategies, including motivational support, Christian role modeling, personal mentoring, reflective activities, collaborative learning, and the implementation of active learning methods. The novelty of this study lies in the integration of Christian values and individualized guidance as an approach to fostering self-confidence that extends beyond academic aspects to students’ overall personal development. Therefore, the strategies implemented by Catholic Religious Education teachers contribute to strengthening students’ confidence, independence, and participation in both classroom learning and social life within the school environment. ABSTRAK Kepercayaan diri merupakan salah satu aspek penting yang mendukung perkembangan akademik dan sosial peserta didik. Dalam konteks pendidikan, peran guru tidak hanya terbatas pada penyampaian materi, tetapi juga mencakup upaya membangun keyakinan siswa terhadap kemampuan dirinya. Penelitian ini mengkaji self-confidence siswa kelas XI dalam pembelajaran Pendidikan Agama Katolik di SMA Katolik Cinta Kasih Tebing Tinggi serta strategi yang digunakan guru untuk mendukung proses tersebut. Kajian dilakukan melalui pendekatan kualitatif deskriptif dengan melibatkan guru Pendidikan Agama Katolik dan siswa kelas XI sebagai sumber data. Informasi diperoleh melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan temuan diperkuat melalui triangulasi sumber dan teknik. Temuan penelitian menunjukkan bahwa siswa memiliki tingkat self-confidence yang baik, yang tercermin dari keberanian mengemukakan pendapat, kemampuan mengelola emosi, kemandirian belajar, serta kesadaran terhadap potensi diri. Kondisi tersebut didukung oleh berbagai strategi guru, seperti pemberian motivasi, keteladanan hidup Kristiani, pendampingan personal, kegiatan refleksi, kerja kelompok, dan penggunaan metode pembelajaran aktif. Kebaruan penelitian terletak pada integrasi nilai-nilai Kristiani dan pendekatan pendampingan individual sebagai sarana pembentukan self-confidence yang tidak hanya menyentuh aspek akademik, tetapi juga perkembangan pribadi siswa secara menyeluruh. Dengan demikian, strategi guru Pendidikan Agama Katolik berkontribusi dalam memperkuat keberanian, kemandirian, dan partisipasi siswa dalam pembelajaran maupun kehidupan sosial di sekolah.